On the description of bistochastic Kadison–Schwarz operators on M2(C) - Mukhamedov, Farrukh; Abduganiev, Abduaziz (World Scientific, 2010)
In this paper we describe bistochastic Kadison-Schawrz operators on M2(C). Such description allows us to ¯nd positive, but not Kadison-Schwarz operators. Moreover, by means of this characterization we can construct Kadison{Schawrz operators which are not completely positive